The SOAR Model as an Effective Mechanism for University–Community Partnerships to End Homelessness. (12th June 2020) - Donaldson, Linda Plitt; Streeter, Calvin L.; Larkin, Heather; Briar-Lawson, Katharine; Meyer-Adams, Nancy; Lupfer, Kristin; Elder, Jen; Grimshaw, Angela
ABSTRACT: University social work programs can play a critical role in helping communities to expand local capacity in efforts to end homelessness. The Supplemental Security Income/Social Security Disability Insurance (SSI/SSDI) Outreach, Access and Recovery (SOAR) program is an evidence-based model that social work programs are advancing through university–community partnerships. SOAR seeks to prevent and end homelessness through increased access to Supplemental Security Income (SSI) and Social Security Disability Insurance (SSDI) for people suffering from chronic homelessness and who also have a disability. This article uses a case study approach to describe an initiative of the National Center on Excellence in Homeless Services designed to use social work education as a mechanism to build local capacity for using SOAR.